No dynamic visual capture for self-translation minimum audible angle - Rummukainen, Olli S.; Schlecht, Sebastian J.; Habets, Emanuël (The Journal of the Acoustical Society of America, 2020)
Auditory localization is affected by visual cues. The study at hand focuses on a scenario where dynamic sound localization cues are induced by lateral listener self-translation in relation to a stationary sound source with matching or mismatching dynamic visual cues. The audio-only self-translation minimum audible angle (ST-MAA) is previously shown to be 3.3° in the horizontal plane in front of the listener. The present study found that the addition of visual cues has no significant effect on the ST-MAA.
CRIS-Team Scopus Importer:2020-08-14